MiR-34a as hub of T cell regulation networks. Issue 1 (16th July 2019) - Hart, Martin; Walch-Rückheim, Barbara; Krammes, Lena; Kehl, Tim; Rheinheimer, Stefanie; Tänzer, Tanja; Glombitza, Birgit; Sester, Martina; Lenhof, Hans-Peter; Keller, Andreas; Meese, Eckart
Abstract : Background: Micro(mi)RNAs are increasingly recognized as central regulators of immune cell function. While it has been predicted that miRNAs have multiple targets, the majority of these predictions still await experimental confirmation. Here, miR-34a, a well-known tumor suppressor, is analyzed for targeting genes involved in immune system processes of leucocytes. Methods: Using an in-silico approach, we combined miRNA target prediction with GeneTrail2, a web tool for Multi-omics enrichment analysis, to identify miR-34a target genes, which are involved in the immune system process subcategory of Gene Ontology. Results: Out of the 193 predicted target genes in this subcategory we experimentally tested 22 target genes and confirmed binding of miR-34a to 14 target genes including VAMP2, IKBKE, MYH9, MARCH8, KLRK1, CD11A, TRAFD1, CCR1, PYDC1, PRF1, PIK3R2, PIK3CD, AP1B1, and ADAM10 by dual luciferase assays. By transfecting Jurkat, primary CD4 + and CD8 + T cells with miR-34a, we demonstrated that ectopic expression of miR-34a leads to reduced levels of endogenous VAMP2 and CD11A, which are central to the analyzed subcategories. Functional downstream analysis of miR-34a over-expression in activated CD8 + T cells exhibits a distinct decrease of PRF1 secretion. Conclusions: By simultaneous targeting of 14 mRNAs miR-34a acts as major hub of T cell regulatory networks suggesting to utilize miR-34a as target of intervention towards a modulation of the immune responsiveness of T-cells in a broad tumor context.